2013
DOI: 10.7567/jjap.52.102101
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Improvement of 630 nm AlGaInP Light-Emitting Diodes based on AlGaAs Bottom Window

Abstract: Metal organic chemical vapor deposition (MOCVD) based aluminum gallium arsenide (AlGaAs) used as the bottom window (BW), which was inserted between the light-emitting diode (LED) structure and the absorbing substrate, has been proposed to improve the extraction efficiency of 630 nm AlGaInP LEDs. In an AlGaInP LED with this AlGaAs BW, enhanced light extraction efficiency was observed, as some of the light emitted from the active region to the absorbing substrate could pass out of the LED through the BW. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The primary epistructure of red LED wafers grown on GaAs substrate is composed of a bottom distributed Bragg reflector (DBR), an AlGaInP MQW sandwiched between two AlInP cladding layers and a GaP window layer. The photon energy of red light is greater than the energy bandgap of the GaAs epilayer, thus the bottom DBRs reflect the downward-emitting photons towards the top surface to avoid substrate absorption [22]. On the other hand, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The primary epistructure of red LED wafers grown on GaAs substrate is composed of a bottom distributed Bragg reflector (DBR), an AlGaInP MQW sandwiched between two AlInP cladding layers and a GaP window layer. The photon energy of red light is greater than the energy bandgap of the GaAs epilayer, thus the bottom DBRs reflect the downward-emitting photons towards the top surface to avoid substrate absorption [22]. On the other hand, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The total internal reflection (TIR) problem leads to only few emitted photons in a narrow escape cone from the active regions; approximately 10% of the light can be extracted from the LED’s surface; approximately 90% of the light is trapped inside the LED 4 and is transformed into heat, which drastically degrades the LED’s performance after long-term operation. Therefore, one of the most crucial issues in AlGaInP-based LED research is increasing the number of photons that escape the active region 5 9 . Several efficient methods have been proposed and demonstrated to increase light extraction efficiency (LEE), such as the use of simple random surface roughness structures 10 , photonic crystal structures 11 , graded reflective index materials 12 , 13 , and embedded (or self-assembled) nanostructures 14 – 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also shown that the efficiency of optical device could be increased by inserting a distribution Bragg reflector (DBR), consisting of n-AlAs and n-(Al 0.5 Ga 0.5 )As, between the device and absorbing substrate [8]. Elsewhere, AlGaAs having a rough 150 μm thickness was used as the transparent substrate in order to fabricate higher efficiency optical devices [9].…”
Section: Introductionmentioning
confidence: 99%